Training periodisation - An obsolete methodology? - Loturco, I.; Nakamura, F. Y. (ASPETAR Sports Medicine Journal, 2016)
It is evident that this article will not resolve the controversies and debates which surround the conceptual basis of training periodisation. However, it highlights a clear need to develop more applied, effective and realistic methods of training (and developing) professional athletes, who compete several times per year and need to maintain near peak performance throughout the macrocycle. Even for athletes and teams with a low number of competitions/matches during a given period, the periodisation concept should be revisited, since its rate of effectiveness to control and attain the athletes` peak performance is very low. From a practical standpoint, monitoring athletes using tests which best correlate to actual sports performance is much more important than following theoretical concepts, which subjectively state that form might be predictable and controlled. With this simple and applied thought, strength and conditioning coaches may select better ways to control fluctuations in the competitiveness of individuals and teams, besides the already well-established variations in traditional training compo-nents (i.e. volume and intensity). It will help coaches to detect unexpected adaptations in the athletes` fitness traits and adjust training loads according to these measured responses. In this regard, the use of validated methods for daily assessment of the internal training loads might be a useful strategy to quantify/modulate training intensity and its respective dose-response relationship with the specific changes in physical qualities64,86. Further studies are necessary to develop more effective and applied methods to train and develop high-level athletes for long-term success, in order to better enhance their form, according to their specific athletic requirements. Finally, coaches are strongly encouraged to seek more accurate and practical methods to control peak performance on a daily basis, guided by feedback from simple measures, since the subjective and empirical concepts of training periodisation are not able to predict this crucial `point` of athletes` training cycles.